The Muslim world in modern South Asia : power, authority, knowledge - Robinson, Francis (Ranikhet Permanent Black, 2019)
This book is primarily concerned with the experience of the Muslim world over the past two hundred years. It considers the challenges which Western dominance has offered key aspects of Muslim civilisation, and Muslim responses to them.
Keywords: Islamic renewal; Islamic renewal